2006
DOI: 10.1098/rspb.2006.0209
|View full text |Cite
|
Sign up to set email alerts
|

Partner choice creates competitive altruism in humans

Abstract: Reciprocal altruism has been the backbone of research on the evolution of altruistic behaviour towards non-kin, but recent research has begun to apply costly signalling theory to this problem. In addition to signalling resources or abilities, public generosity could function as a costly signal of cooperative intent, benefiting altruists in terms of (i) better access to cooperative relationships and (ii) greater cooperation within those relationships. When future interaction partners can choose with whom they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
377
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 417 publications
(424 citation statements)
references
References 33 publications
15
377
3
2
Order By: Relevance
“…The supporting experiment's aim was to demonstrate that (i) public information and (ii) partner choice increased cooperative reputation-building behaviour. Our findings were consistent with those of earlier studies including Barclay & Willer (2007) and are therefore described in the electronic supplementary material. The main experiment consisted of two stages in which participants first had an opportunity to build up reputation (stage 1) and could then make use of the information about other players' reputations in order to choose partners for further interactions.…”
Section: Introductionsupporting
confidence: 93%
“…The supporting experiment's aim was to demonstrate that (i) public information and (ii) partner choice increased cooperative reputation-building behaviour. Our findings were consistent with those of earlier studies including Barclay & Willer (2007) and are therefore described in the electronic supplementary material. The main experiment consisted of two stages in which participants first had an opportunity to build up reputation (stage 1) and could then make use of the information about other players' reputations in order to choose partners for further interactions.…”
Section: Introductionsupporting
confidence: 93%
“…Similarly, Nelissen (2008) found that those who paid higher costs to punish noncooperators received greater trust in subsequent dyadic interactions. Barclay and Willer (2007) used a dyadic prisoners dilemma game with varying opportunities for partner choice and signaling of cooperative intent for future rounds with observers; they found that subjects were more generous when they stood to benefit from being chosen for cooperative partnerships, and the most generous subjects were correspondingly chosen more often as partners. Similarly, Bereczkei, Birkas and Kerekes (2007) demonstrated that subjects were more willing to make charity offers in the presence of their group mates than in anonymous situations and that those donors received significantly higher scores than others on scales measuring sympathy and trustworthiness.…”
Section: Signaling Strategiesmentioning
confidence: 99%
“…One 25 way this can be achieved is if helpful individuals are preferred as partners: giving players the option to either avoid bad partners or actively choose good ones increases cooperation, compared to interactions where individuals are forced to interact with one another [1][2][3][4][5]. Biological market theory [5][6][7] predicts that individuals prefer the 'best' possible partners for interactions.…”
Section: Introductionmentioning
confidence: 99%